1997
DOI: 10.1126/science.276.5314.952
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Protein Phosphatase 2A by Direct Interaction with Casein Kinase 2α

Abstract: Timely deactivation of kinase cascades is crucial to the normal control of cell signaling and is partly accomplished by protein phosphatase 2A (PP2A). The catalytic (alpha) subunit of the serine-threonine kinase casein kinase 2 (CK2) bound to PP2A in vitro and in mitogen-starved cells; binding required the integrity of a sequence motif common to CK2alpha and SV40 small t antigen. Overexpression of CK2alpha resulted in deactivation of mitogen-activated protein kinase kinase (MEK) and suppression of cell growth.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
204
3

Year Published

1998
1998
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(223 citation statements)
references
References 25 publications
15
204
3
Order By: Relevance
“…Our observations coincide with a number of recent studies documenting PP-2A association with different kinases [12][13][14][15][16][17][18][19][20][21][22]. For example, studies by Heriche et al [12] indicate that casein kinase 2α associates with PP-2A and causes activation of PP-2A.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our observations coincide with a number of recent studies documenting PP-2A association with different kinases [12][13][14][15][16][17][18][19][20][21][22]. For example, studies by Heriche et al [12] indicate that casein kinase 2α associates with PP-2A and causes activation of PP-2A.…”
Section: Discussionsupporting
confidence: 92%
“…For example, studies by Heriche et al [12] indicate that casein kinase 2α associates with PP-2A and causes activation of PP-2A. A recent study by Westphal et al [43] indicates that PP-2A forms complexes with p70 S6 kinase, p21-activated kinase-1 (PAK-1) and p21-activated kinase-3 (PAK-3) in i o.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been shown that PP2A can form complexes with CKII or a calciumcalmodulin-dependent kinase (Heriche et al 1997;Westphal et al 1998), suggesting that phosphorylation and dephosphorylation of cellular proteins are tightly coupled. Interestingly, both CKII and a calciumcalmodulin-dependent kinase were shown to be FRQ kinases in Neurospora (Yang et al 2001, raising the possibility that the functions of CKII and CAMK-1 in FRQ phosphorylation are regulated by PP2A.…”
Section: Genes and Development 257mentioning
confidence: 99%
“…The enzyme is described as a multi-subunit protein kinase that is generated by the association of two catalytic subunits a or a 0 with a dimer of b regulatory subunits leading to the idea that CK2 functions as a stable heterotetrameric complex. However, this traditional view has been challenged by the evidence for naturally occurring free monomeric CK2a (Dobrowolska et al, 1992;Stigare et al, 1993;Heriche et al, 1997) and for an unbalanced expression of CK2 subunits in different mammalian tissues (Stalter et al, 1994;Pinna and Meggio, 1997;Guerra et al, 1999b;Ghavidel and Schultz, 2001;Keller et al, 2001). Moreover, the marked elevation of CK2 enzymatic activity in various solid tumors is suspected to result in the suppression of cellular apoptosis, aiding tumor resistance to radiation and anticancer drug treatments (Guerra and Issinger, 1999;Ahmed et al, 2002).…”
Section: Introductionmentioning
confidence: 99%